1976
DOI: 10.1177/028418517601700106
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angiography with Diatrizoate and Metrizamide

Abstract: The non-ionic contrast medium metrizamide produced a smaller coronary flow increase than the ionic medium diatrizoate after injection into the main left coronary artery in dogs and had also a shorter transit time through the coronary vessels. The coronary veins were better filled with metrizamide. The reduced coronary flow effects of metrizamide compared to ionic contrast medium and the improved venous filling makes metrizamide a favorable contrast material for use in coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Metrizamide (low osmolality) causes a smaller increase in coronary flow than diatrizoate.23 Interestingly, the contrast washout time may, however, be faster with metrizamide, perhaps reflecting less red cell rigidification. 22 This results in venous phase films of better quality. The role of cholinesterase inhibition7 in the response of the coronary circulation has not been evaluated.…”
Section: Effects On Cardiac Haemodynamics and Coronary Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Metrizamide (low osmolality) causes a smaller increase in coronary flow than diatrizoate.23 Interestingly, the contrast washout time may, however, be faster with metrizamide, perhaps reflecting less red cell rigidification. 22 This results in venous phase films of better quality. The role of cholinesterase inhibition7 in the response of the coronary circulation has not been evaluated.…”
Section: Effects On Cardiac Haemodynamics and Coronary Flowmentioning
confidence: 99%
“…In the dog the severity of the depressant effects has been substantially reduced with the low osmolality agents when compared with conventional hyperosmolar agents,'8 22 and other comparative studies have shown differences in the magnitude of the depressant effects produced even by different commercial preparations of the conventional agents. 23 The part played by simple myocardial oxygen deprivation during coronary angiography appears to be unimportant.…”
Section: Effects On Cardiac Haemodynamics and Coronary Flowmentioning
confidence: 99%